Pengaruh organizational citizenship behaviour terhadap kinerja anggota Kepolisian - Virania Nadindra Puspamaya Dotulong; Devina Andriany (Cognicia, 2021)
≤   Performance problems of police members are influenced by a very heavy workload, incompatibility with passion, and personal issues. Those performance problems determine organizational citizenship behavior. Therefore this research was done to know the effect of organizational citizenship behavior toward the work performance of police members. This research is quantitative research with a survey design. The subjects are 200 members of the Indonesian National Police. The sampling technique used purposive sampling. The analysis in this study used simple linear regression analysis. The results of this study provided evidence to accept the hypothesis that there is a significant positive impact between organizational citizenship behavior on performance (β = 0.41, p<0.001), the higher organizational citizenship behavior, the higher the performance of police personnel.   Keywords: Indonesian national police, organizational citizenship behaviour, performance